Inferior vena cava ultrasound in acute decompensated heart failure: design rationale of the CAVA‐ADHF‐DZHK10 trial. (28th January 2020) - Jobs, Alexander; Vonthein, Reinhard; König, Inke R.; Schäfer, Jane; Nauck, Matthias; Haag, Svenja; Fichera, Carlo Federico; Stiermaier, Thomas; Ledwoch, Jakob; Schneider, Alisa; Valentova, Miroslava; von Haehling, Stephan; et al.
Abstract: Aims: Treating patients with acute decompensated heart failure (ADHF) presenting with volume overload is a common task. However, optimal guidance of decongesting therapy and treatment targets are not well defined. The inferior vena cava (IVC) diameter and its collapsibility can be used to estimate right atrial pressure, which is a measure of right‐sided haemodynamic congestion. The CAVA‐ADHF‐DZHK10 trial is designed to test the hypothesis that ultrasound assessment of the IVC in addition to clinical assessment improves decongestion as compared with clinical assessment alone. Methods and results: CAVA‐ADHF‐DZHK10 is a randomized, controlled, patient‐blinded, multicentre, parallel‐group trial randomly assigning 388 patients with ADHF to either decongesting therapy guided by ultrasound assessment of the IVC in addition to clinical assessment or clinical assessment alone. IVC ultrasound will be performed daily between baseline and hospital discharge in all patients. However, ultrasound results will only be reported to treating physicians in the intervention group. Treatment target is relief of congestion‐related signs and symptoms in both groups with the additional goal to reduce the IVC diameter ≤21 mm and increase IVC collapsibility >50% in the intervention group. The primary endpoint is change in N‐terminal pro‐brain natriuretic peptide from baseline to hospital discharge. Secondary endpoints evaluate feasibility, efficacy of decongestion on other scales, and the impact of the intervention on clinical endpoints. Conclusions: CAVA‐ADHF‐DZHK10 will investigate whether IVC ultrasound supplementing clinical assessment improves decongestion in patients admitted for ADHF.